Authority Notary Of Making Land Deeds - Eko Prasetyo, Wengky (International Significance of Notary, 2024)
Abstract : The authority of the Land Agency of the Republic of Indonesia is based on the regulation of the President of the Republic of Indonesia Number 10 of 2006 concerning the National Land Agency, Article 2 states: The National Land Agency of the Republic of Indonesia carries out the duties of the Government in the field of land nationally,  sectorally, regionally. Based on the description above, the author's goals in this study are to find out and analyze what is the basis of the Notary's authority in making land-related deeds, as well as to find out and analyze the form of Notary's authority in making land-related deeds. To answer the problems studied, the author uses normative juridical legal research. The approach used by the author in this study is a statutory approach (Statute Approach), and a conceptual approach (Conceptual Approach). The results show that the meaning of the deed related to land which is the authority of the Notary is narrow, meaning that the Notary can make a deed related to land as long as the deed is not the authority of the PPAT. In this study, it was concluded that the authority of the Notary in making the deed related to land is stated in Article 15 paragraph (2) letter f of the UUJN, but in his authority it is also limited because there are other officials who are given the authority to make the deed on land, namely the Land Deed Maker Officer. (PPAT).Keywords: Notary; PPAT; Deed, Land.